The burden of systemic therapy administration route in treating HER2-positive breast cancer (for patients, healthcare professionals, and healthcare system): a systematic literature review - Landeiro, Luciana Castro Garcia; Martins, Tamie de Camargo; Grigolon, Ruth Bartelli; Monteiro, Isabel; Balardin, Joana Bisol; Padilha, Eduardo; Amorim, Gilberto; Stefani, Stephen (Frontiers in Pharmacology, 2024)
Introduction: Breast cancer (BC) is one of the leading causes of cancer and is the first cause of death from malignant tumors among women worldwide. New cancer therapies receive regulatory approval yearly and to avoid health disparities in society, the health systems are challenged to adapt their infrastructure, methodologies, and reimbursement policies to allow broad access to these treatments. In addition, listening to patients' voices about their therapy preferences is essential. We aim to investigate the administration route preferences (subcutaneous [SC] or intravenous [IV]) among patients diagnosed with HER2 positive BC and healthcare professionals (HCPs) and to investigate healthcare resources utilization (quality and quantity) for each route of administration (SC or IV) for treating those patients. Methods: We conducted a systematic literature review focused on clinical trials and observational and economic studies, using PubMed (MEDLINE), Cochrane Library, Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), and Latin American and Caribbean Health Sciences Literature (LILACS) databases based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Results: The literature review included 25 studies in the analysis. Studies have reported that patients and HCPs prefer the SC route of administration to IV because it saves time in terms of chair time, administration, and preparation and is less painful. In addition, SC administration might be a more cost-saving option when analyzing direct and indirect costs. Discussion: As BC stands as a significant global health concern and the leading cause of cancer-related deaths in women worldwide, understanding and incorporating patient and HCPs preferences in the choice of administration route become paramount. The observed preference for SC administration not only aligns with the imperative of adapting health systems to facilitate broad access to new cancer therapies but also underscores the importance of considering Código de campo alterado 2 patient experiences and economic implications in shaping treatment strategies. These insights are crucial for healthcare policymakers, clinicians, and stakeholders in optimizing healthcare resources and enhancing the overall quality of BC care.